K-edge subtraction imaging for coronary angiography with a compact synchrotron X-ray source - Kulpe, Stephanie; Dierolf, Martin; Braig, Eva; Guenther, Benedikt; Achterhold, Klaus; Gleich, Bernhard; Herzen, Julia; Rummeny, Ernst; Pfeiffer, Franz; Pfeiffer, Daniela (PLoS ONE, 2018)
About one third of all deaths worldwide can be traced back to cardiovascular diseases. An interventional radiology procedure for their diagnosis is Digital Subtraction Angiography (DSA). An alternative to DSA is K-Edge subtraction (KES) imaging, which has been shown to be advantageous for moving organs and eliminating image artifacts caused by patient movement. As highly brilliant, monochromatic X-rays are required for this method, it has been limited to synchrotron facilities so far, restraining the feasibility in clinical routine. Compact synchrotron X-ray sources based on inverse Compton scattering, which have been evolving substantially over the past decade, provide X-rays with sufficient brilliance that meet spatial and financial requirements affordable in laboratory settings or for university hospitals. In this work, we demonstrate a first proof-of-principle K-edge subtraction imaging experiment using the Munich Compact Light Source (MuCLS), the first user-dedicated installation of a compact synchrotron X-ray source worldwide. It is shown experimentally that the technique of KES increases the visibility of small blood vessels overlaid by bone structures.
CRIS-Team Scopus Importer:2023-03-08